Effects of surfactants/stabilizing agents on the microstructure and properties of porous geopolymers by direct foaming - Yingjie Qiao; Xinyu Li; Chengying Bai; Hongqiang Li; Jinghao Yan; Yi Wang; Xiaodong Wang; Xiaohong Zhang; Ting Zheng; Paolo Colombo (Journal of Asian Ceramic Societies, 2021)
Metakaolin-based porous geopolymers were synthesized by direct foaming using various surfactants/stabilizing agents with or without chemical pore-forming agent (hydrogen peroxide). The effects of surfactants/stabilizing agents and solid loading on their pore morphology, density, porosity, and some properties, such as thermal conductivity and compression strength, were investigated. Experimental data and different theoretical models were successfully applied to evaluate both compression strength (σ) and effective thermal conductivity (λ) as a function of porosity (ε). Porous geopolymers with higher ε presented both a lower value of mechanical strength and improved thermal conductivity performance. The variation of σ with ε could be well described by the minimum solid area (MSA) model, and the variation of λ with ε was found to be more accurately described using a universal model derived from the five basic models.